Public Knowledge, Attitude And Acceptability of COVID-19 Vaccine among Traders in Wuse Market Abuja: A Cross-Sectional Study - Akafa, Tensaba Andes; Oladele, Gloria Omonefe; Iseko, Kingsley Iyoko; Akafa, Vika Tensaba; David, Izam Emmanuel; Ujah, Oche Williams; John, Tongle Nanle; Nanmar, Chakfa; Tyem, Lawal Danjuma; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
The effect of the COVID-19 pandemic on public health has been unpleasant. Vaccination is a critical measure to decrease COVID-19 economic loss and public health burden. This is very helpful to control the COVID-19 pandemic. The process of halting COVID-19 solely depends on population uptake of the vaccination process and the adoption of non-pharmacological measures. This in turn relies on the public willingness to get vaccinated. The public acceptability of this vaccination is further determined by the level of knowledge and trust in currently available COVID-19 vaccines. Therefore, this paper aims to discuss the findings of public knowledge, attitude, and acceptability of COVID-19 vaccines among traders in Wuse Market Abuja. A cross-sectional study was conducted among different traders in the Abuja Wuse Market to assess their knowledge, attitude and level of acceptability toward COVID-19 vaccinations using a self-administered survey questionnaire with the following four sections; socio-demographic characteristics, knowledge assessment questions, attitude assessment, and acceptability questions. A total of 166 participants completed the questionnaire. The knowledge of the COVID-19 vaccinations among the study participants was high with 143(86%) respondents stating that they knew about COVID-19 vaccinations. Among the traders that participated, 74(44.36%) believed that vaccines are safe and 109 (66.02%) agreed that vaccines are critical to protect the public from COVID-19 infection. But only, 45 (27.4%) accept to receive the vaccine. Participants’ attitudes, knowledge, and level of acceptability were significantly affected by age, gender, education level, and marital status (P <0.001). Our findings suggest that there is good knowledge and attitude toward the vaccination process against COVID-19 among study participants in spite of low acceptability. Awareness campaigns are therefore necessary to disseminate reliable knowledge about COVID-19 vaccines and demystify the COVID-19 conspiracy theory in order to raise the level of vaccination acceptance.